Religious Social Capital in Creating Peace Values in Multicultural Societies - Munawwaroh, Siti Madinatul; Kustana, Kustana (Jurnal Iman dan Spiritualitas, 2026)
Indonesia's cultural and ethnic diversity holds great potential for social integration, but is also prone to conflict. In this context, religion plays a dual role: it can be both a trigger for tension and a bridge for peace. This study examines the role of religion as social capital in fostering harmony in a pluralistic society. The approach used was a qualitative literature study, analyzed thematically. The results indicate that religious social capital plays a crucial role in fostering peace in multicultural societies through three main elements: religious networks, social trust, and the integration of religious values with local culture, which fosters harmony. Concrete findings are demonstrated through studies of various communities such as peaceful Islamic boarding schools (pesantren), the Forum for Interfaith Harmony (FKUB), and the Gusdurian network, which implement inclusive education, open religious practices, and interfaith advocacy. These three elements form the foundation of social reconciliation based on spirituality and local wisdom, and demonstrate that religious organizations such as Nahdlatul Ulama (NU) and Muhammadiyah can become agents of peace if they prioritize an inclusive and contextual approach. This study enriches social capital theory by integrating religious and local values, and offers a new direction in the development of inclusive Islamic education and interfaith dialogue relevant to societal realities.